Enhancing Purchase Decisions: The Role of E-WOM, Online Customer Review, and Free Shipping Promotion - Vitara, Anisa Fajar; Puspa Novita Sari (Journal of Economics and Business Research (JUEBIR), 2024)
Online shopping has become an integral part of daily life in this digital era. One of the increasingly popular platforms for shopping is TikTok Shop, which combines entertainment and e-commerce. This study aims to analyze the influence of E-WOM, online customer reviews, and free shipping promotions on purchase decisions on TikTok Shop. This research uses a quantitative approach. The sample for this study is consumers of Wardah cosmetic products who made purchases on TikTok Shop. The sampling technique used in this research is non-probability sampling, resulting in 115 respondents. The findings of this study reveal that: 1) E-WOM has a positive and significant influence on the purchase decisions of Wardah products on the TikTok Shop application. This indicates that Wardah has optimally utilized the E-WOM feature on TikTok Shop. 2) Online customer reviews affect the purchase decisions of Wardah products on the TikTok Shop application. 3) Free shipping promotions also have a positive and significant impact on the purchase decisions of Wardah products on the TikTok Shop application. Wardah's decision to offer free shipping promotions is a strategic move to boost the sales of Wardah products.